Insights into melatonin-induced photosynthetic electron transport under low-temperature stress in cucumber - Wu, Pei; Ma, Yadong; Ahammed, Golam Jalal; Hao, Baoyu; Chen, Jingyi; Wan, Wenliang; Zhao, Yanhui; Cui, Huimei; Xu, Wei; Cui, Jinxia; Liu, Huiying (Frontiers in Plant Science, 2022)
In this study, the differences in OJIP and MR820 of cucumbers were probed to demonstrate an insight into the precise influence of MT on cucumber photosystems under low temperature stress. We pre-treated cucumber seedlings with different levels of MT before imposing low temperature stress (10 ℃ /6 ℃). The results indicated that moderate concentrations of MT had a positive effect on the growth of cucumber seedlings. MT 100 improved the PIabs, the OEC centers and electron transport between PSII and PSI, mainly by decreasing the L-band, K-band, and G-band, but showed differences with different duration of low temperature stress. In addition, these indicators related to quantum yield and energy flux of PSII regulated by MT indicated that MT 100 effectively protected the electron transport and energy distribution in the photosystem. According to the results of WO-I ≥ 1 and MR820 signals, MT also affected PSI activity. MT 100 decreased the minimal value of MR/MRO and the oxidation rate of PC and P700 (Vox), while increased △MRslow/MRO and deoxidation rates of PC+ and P700+ (Vred). The loss of the slow phase of MT 200 and MT 400-treated plants in the MR820 kinetics was due to the complete prevention of electron movement from PSII to re-reduce the PC+ and P700 +. These results suggest that appropriate MT concentration can improve the photosynthetic performance of PS II and electron transport from QA to QB, promote the balance of energy distribution, strengthen the connectivity of PSI and PSII, improve the electron flow of PSII via QA to PC+ and P700+ from reaching PSI by regulating multiple sites of electron transport chain in photosynthesis, and increase the pool size and reduction rates of PSI in low temperature-stressed cucumber, All these modifications by MT 100 treatment promoted the photosynthetic electron transfer smoothly, and further restored the cucumber plant growth under low temperature stress. Therefore, we conclude that spraying MT at an appropriate concentration is beneficial for protecting the photosynthetic electron transport chain, while spraying high concentrations of MT has a negative effect on regulating the low temperature tolerance in cucumber.